Anti-Drug Education Act of 1990. House of Representatives, 101st Congress, 2d Session - Congress of the U.S., Washington, DC. House Committee on Education and Labor; Congress of the U.S., Washington, DC. House Committee on Education and Labor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This document is a congressional report on the Anti-Drug Education Act of 1990, House of Representatives (H.R.) 5124 which enhances current Federal efforts to prevent and eliminate drug abuse among American youth by expanding and improving drug abuse education, prevention and counseling services, and by providing positive alternative activities to drug use and abuse. It is noted that the bill will also improve security for students and provide incentives for more Americans to choose law enforcement as a career. This report contains a section-by-section summary of the amendment in addition to the enacting clause of the bill. The new text is inserted in italics. These topics are discussed: funding; committee consideration; need for the legislation; major provisions of the bill, including replication of successful drug abuse education programs, support of school-based counseling programs, support of school-based and recreational activities, ensuring the safety of students, and police recruitment; oversight; cost estimate; committee estimate; and inflationary impact statement. Additional dissenting views by William F. Goodling and Thomas E. Petri are included. (ABL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alcohol Abuse; Drug Abuse; Drug Education; Elementary School Students; Elementary Secondary Education; Federal Legislation; Financial Support; Law Enforcement; Prevention; School Counseling; School Security; Secondary School Students; Drug Free Schools; Congress 101st -- Drug Free Schools and Communities Act 1986; Legal/Legislative/Regulatory Materials; Reports, General